Identification of Leading Sectors in Regional Economic Development in Kapuas Hulu District - Bella Widya Pertiwi (International Journal of Economics Development Research (IJEDR), 2023)
This research was conducted in Kapuas Hulu District which is located in West Kalimantan Province and borders with Malaysia. The purpose of this research was conducted to determine the right strategy to see the base sector which has the potential to become a leading sector and the productivity of the leading sector which can provide a reference for regional development of Kapuas Hulu Regency to the local government. government. This study also uses a quantitative descriptive method with Location Quotient analysis, Shift Share analysis and Tipologi klassen analysis. The research data used is time series data in the form of PDRB of Kapuas Hulu Regency and West Kalimantan Province from 2015 to 2019 based on constant base prices. The research found that in the LQ analysis there were 6 sectors based on the second analysis there were 7 sectors that had positive values ??and had comparative advantages and in the final analysis there were 2 sectors that experienced advanced and fast growth. Leading sector and economic potential in Kapuas Hulu Regency is the construction sector which has a positive value in each technical analysis.